An analysis of intra-sentential switching used by Youtuber: Livjunkie - Meza Andika; Merry Rullyanti (Literary Criticism, 2020)
Code switching can be produced by bilingual users including a Youtuber. The researcher analysed the switching by a bilingual Youtuber namely Livjunkie. Within the title of “An Analysis of Intra -Sentential Switching Used by a Youtuber: Livjunkie”, the discussion of this research deals with the number of utterances. The objectives of this research are to find out types of word included as intra-sentential switching used by Livjunkie, the most frequently occuring word included as intra-sentential switching used by Livjunkie, and the meaning of the word frequently used by Livjunkie included as intra-sentential switching. This research was designed to use descriptive qualitative method. This research was carried out by taking steps to collect data, classify data, analyze data, and make conclusions. The data analysis technique that was used is based on Spradley’s theory. The researcher found 9 types of words appreared in intra-sentential switching used by Livjunkie in her selected Youtube videos. They are Noun, Adjective, Conjunction, Adverb, Verb, Exclamation, Preposition, Numeral, and Determiner. There are 707 nouns found in this research. The percentage is 57.71 %. It is the highest value of all. There is only 1 determiner found in this research. The percentage is 0.08 %. It is the lowest value of all. It was also found that there are 1223 data that have denotative meanings and there are 2 data that have connotative meanings. It was analyzed that Livjunkie used English words within a clause or sentence in Bahasa Indonesia. The results also show that the kinds of meaning found are mostly included in denotative meaning instead of connotative meaning. Beside that, the videos themselves show the phenomenon of bilingualism. It is hoped that the results will be useful for the development of linguistics especially in English letters or Sociolinguistics.